2008
DOI: 10.1007/s10565-008-9111-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term vitamin A supplementation at therapeutic doses induces a pro-oxidative state in the hepatic environment and facilitates calcium-ion-induced oxidative stress in rat liver mitochondria independently from permeability transition pore formation

Abstract: There is a growing body of evidence showing that vitamin A induces toxic effects in several experimental models and in human beings. In the present work, we have investigated the effects of short-term vitamin A supplementation on the adult rat liver redox status. We have found that vitamin A at therapeutic doses induces a hepatic oxidative insult. Furthermore, we have observed increased antioxidant enzyme activity in the liver of vitamin-A-treated rats. Additionally, some mitochondrial dysfunction was found si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
8
2
Order By: Relevance
“…For SOD activity, our results are not in agreement to other works, since we observed decreased activity after 3 and 28 days treatment period (no modifications after 7 days) while there was a reported increased SOD activity in liver (acutely and chronically) and hypothalamus (chronic period) [10][11][12]. However, one more time we have to consider the organ analyzed and the fact that a very few studies have done oxidative stress parameters analysis in vascular level.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…For SOD activity, our results are not in agreement to other works, since we observed decreased activity after 3 and 28 days treatment period (no modifications after 7 days) while there was a reported increased SOD activity in liver (acutely and chronically) and hypothalamus (chronic period) [10][11][12]. However, one more time we have to consider the organ analyzed and the fact that a very few studies have done oxidative stress parameters analysis in vascular level.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, SH is increased just after 3 days treatment period, the unique period that TBARS had no changes, and did not play modifications after 7 or 28 days treatment period, the same one in which TBARS is diminished [25]. The results presented here, in part, are in accordance to previous works, which found no modifications on SH content after 7 or 28 days treatment period, with identical doses to those tested here, but a difference is notated after 3 days, since in the present study was observed an increase while in the prior a decrease was found [11,12]. Despite the opposite results after 3 days, a coincidence is played, it is exactly in this period that occur the changes, independently if it is to up or down.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, recent studies have provided evidence that retinol could enhance carcinogenesis, especially at doses that exceed the normal dietary intake or in conditions of enhanced oxidative stress (40)(41)(42)(43). This evidence would be supported by the results of a number of experimental studies in different biological systems, in vivo and in vitro, showing that pro-vitamin A, β-carotene, retinol and retinoids have pro-oxidant properties, which might lead to cell oxidative damage and carcinogenesis (44)(45)(46)(47)(48). Thus, in the present scenario of apparently contradictory evidence, further research is needed in order to elucidate the mechanism(s) by which retinoids may influence human carcinogenesis.…”
Section: Discussionmentioning
confidence: 93%